French exploration and intentions with regard to the west coast of Australia 1772–1829 - Reid, Dorothy V (Curtin University, 2008)
In 1772 French navigator Alesno de Saint-Aloüarn, visited the western coast of the Australian continent, and claimed it for France. Some French authorities and later French navigators believed that Saint-Aloüarn’s claim was valid under prescriptive law, yet this law is only valid if the land claimed is settled within a time frame of thirty years. However, France did not intend to either lay claim to, or establish a colony in western Australia during later voyages of exploration conducted in the eighteenth and early nineteenth centuries, especially as in 1778 Captain Cook had taken possession of the east coast of Australia which was fortified by the British Navy. While this thesis does not dispute Saint-Aloüarn’s claim, a long succession of writing developed from a British perspective has located rivalry and fear of French colonial ambitions as the cause for British occupation of western Australia. French, Dutch and British voyages to the west coast of Australia have been canvassed, drawing upon both contemporary accounts and twentieth century interpretations of the aims and motives of the respective governments. This thesis investigates three factors considered to have significantly influenced the motivation for and preparation of relevant French and British voyages of exploration covering the period 1772 to 1829.Differences between concepts held by both nations, such as spatiality and territoriality, the value of science, together with the fact that Britain and France operated under two quite distinct legal systems in regard to territorial claim, form the basis for arguing against past historical understandings. It is argued that while the primary aim of British exploration was to establish colonies to satisfy economic and defence requirements, as well as expansion of the empire, French voyages of exploration undertaken to the west of the Australian continent after 1778 were for scientific purposes. By adding knowledge of a largely unknown part of the continent to the world at large, the French hoped to restore national pride after their humiliating loss at the Battle of Waterloo in 1815, which effectively ended the Napoleonic Wars. The corollary is that the rivalry factor, often put forward by historians as the reason for British annexation of Western Australia in 1829, is shown to be of little value against the other three factors.